Effect of Bamboo Flour on Flame Retardancy and Smoke Suppression of Polypropylene/Ammonium Polyphosphate Composites - Liu, Yide; Li, Hongzhou; Chen, Qinghua; Luo, Fubin; Cao, Changlin (Frontiers in Materials, 2020)
In this paper, the flame-retardant Polypropylene (PP) composites were prepared by melt blending. Ammonium Polyphosphate (APP) and bamboo flour (BF) were selected as flame retardant and smoke suppressant of the composite material. Among them, BF as a synergist can effectively improve the flame retardancy and smoke suppression effect of PP/APP composites. The effects of BF on the mechanical properties, crystallization behavior, thermal degradation, flame retardancy, and especially the smoke suppression effect of PP/APP composite materials were studied. thermogravimetric analysis, limiting oxygen index, cone calorimetry, scanning electron microscopy and other characterization methods were used to study the thermal stability, flame retardancy and combustion characteristics of the composites and the microscopic morphology of carbon residue. Experimental results showed that when the total addition amount of APP/BF (2:1) in PP55/APP30/BF15 composite is 45%, the residual carbon had more specific surface area and micro-pores, which causes the composite to have the best smoke suppression effect. The PHRR of the PP55/APP30/BF15 composite was reduced to 308.2 kW/m2 and the amount of carbon residue was 25%. The continuous carbon layer, formed during combustion can effectively protect the matrix material and prevent the transfer of heat.